Process optimization with Box-Behnken experimental design for photocatalytic degradation of thiamethoxam using perlite supported TiO2 - Ngaha, Emmanuel; Sayen, Stephanie; Guillon, Emmanuel; Duranoglu, Dilek (ELSEVIER SCIENCE INC, 2019)
Effective photocatalytic degradation of thiamethoxam (THX) at low concentration was achieved by using perlite supported TiO2 composite material (PST). Box-Behnken experimental design method was employed in order to evaluate the effect of process parameters and also optimize them. Accordingly, effects of three process parameters (pH, load of PST [PT {g/L}], and air flow rate [AF {L/h}]) were investigated on two responses: (i) the THX degradation percentage after 270 min (DEG270 [%]) and (ii) the electric energy per order (EE/O [kWh/m(3)]). THX degradation was improved by decreasing pH value and increasing air flow rate. Increasing load of PST increased the degradation percentage until a critical value of about 8 g/L, then caused a decrease. Statistically significant second-order polynomial models were developed by regression analysis of experimental data. Optimum conditions were obtained as follows: pH 4, PT 8.30 g/L and AF 18 L/h for an initial THX concentration of 1.46 ppm. These conditions led to a response of 87% +/- 5% for DEG270 and 120 +/- 21 kWh/m(3) for EE/O. Control experiments confirmed a good optimized process and reusability of PST without any regeneration step.
Keywords: Thiamethoxam; Photocatalytic degradation; Perlite; Process optimization; Box-Behnken design; NEONICOTINOID INSECTICIDES; WATER; KINETICS; MECHANISM; ADSORPTION; OXIDATION; GRANULES; CARBON; Engineering; Water Resources